Experimental study of secondary emission radioisotope current source prototype - Kononenko, S.I.; Kalantaryan, O.V.; Kolesnik, V.T.; Muratov, V.I.; Karas, V.I.; Filippenko, V.E. (Вопросы атомной науки и техники, 2008)
The results of experimental investigations of prototype of secondary emission radioisotope current source are presented. Novel physical idea of nuclear particle energy conversion into electricity by means of secondary ion induced electron emission underlies this autonomous power supply. As primary particles we used H+ ion beam from Van de Graff accelerator with megaelectronvolt energy. Some possible regimes of the prototype operation were studied. It was shown that load curve of the prototype had maximum. Output power up to 10 mWatt was obtained. It was experimentally shown realizability of the energy conversion idea.